Thyroid Disorders in Reproductive Females with Abnormal Uterine Bleeding - Javaria Gulzar, Nayla Salman, Danish Sohail, Zill E Huma, (Pakistan Journal of Medical & Health Sciences, 2023)
Methodology: One hundred outpatient females who were having difficulties related to their thyroid bleeding were accepted into the study. Patients with ages ranging from 40 to 55 years were included in this study. Every lady was evaluated to establish whether or not she was suffering from abnormal uterine bleeding, and her thyroid profile was analyzed as well. The procedure for the research study consisted of getting a detailed history from the participants regarding any anomalies in their periods. In addition to these, standard blood tests including random blood sugar, haemoglobin, erythrocyte sedimentation rate, liver function test, pap smear, bleeding time, clotting time, endometrial biopsy, transvaginal ultrasonography and transabdominal, serum T3 (T3), T4 (T4), and thyroid stimulating hormone (TSH) were performed. These tests were carried out on the patient. Results: Mean age as 46.8+5.98 years and mean BMI was calculated as 27.98+6.21(kg/m2). Mean TSH levels were 4.4+2.5(mIU/L), T3 level were 3.4 ± 1.7 (pmol/L), and T4 level were 1.8 ± 0.6 (pmol/L). We found Menorrhagia as the commonest bleeding pattern 49(49%) followed by Oligomenorrhea in 30(30%), Hypomenorrhea in 11(11%) and Metrorrhagia in 2(2%) of the cases. Conclusion: Among the patients with abnormal uterine bleeding, hypothyroidism was common finding and hyperthyroidism was associated with lesser amount of bleeding. Moreover abnormal BMI is a major risk factor for the abnormal uterine bleeding. Keywords: Abnormal uterine bleeding, hypothyroidism, body mass index